2005
DOI: 10.2225/vol8-issue3-fulltext-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards genomic. Research in four Latin American countries

Abstract: The present reflection refers to data obtained about the social representations of genomic research and its applications through interviews with legislators and lawyers, biomedical researchers and civilians and the review of scientific and legal literature in four Latin American countries: Argentine, Chile, Mexico and Peru. Several issues are addressed: little access to prevention and therapeutic methods, lack of equity in health benefits, commercialization of gene sequences through patents which lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In fact, several studies document a robust link between GFs and fear (Jagadeesan and Salem, 2015; Ronteltap et al , 2007; Lusk et al , 2006). For instance, some authors found that people’s general neophobia was correlated with their concerns and negativity regarding novel food technologies (Defez, 2016; Wunderlich and Gatto, 2015; Šorgo and Ambrožič-Dolinšek, 2010; Yunta et al , 2005; Pardo et al , 2002). Opposition to other forms of new technology has its roots in fear and, accordingly, fear and general distress are highly inter-correlated (Valente and Chaves, 2018; Boccia, 2015; Sadler and Zeidler, 2005; Scholderer and Frewer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies document a robust link between GFs and fear (Jagadeesan and Salem, 2015; Ronteltap et al , 2007; Lusk et al , 2006). For instance, some authors found that people’s general neophobia was correlated with their concerns and negativity regarding novel food technologies (Defez, 2016; Wunderlich and Gatto, 2015; Šorgo and Ambrožič-Dolinšek, 2010; Yunta et al , 2005; Pardo et al , 2002). Opposition to other forms of new technology has its roots in fear and, accordingly, fear and general distress are highly inter-correlated (Valente and Chaves, 2018; Boccia, 2015; Sadler and Zeidler, 2005; Scholderer and Frewer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Emotions are often hidden in related concepts, such as concern (James, 2004), moral acceptability (Črne-Hladnik et al 2009), personal or general risk and uncertainty (Finucane, 2002;Ronteltap et al 2007;Christoph et al 2008). The most frequently reported emotions concerning GMOs are negative ones such as worry (anxiety) (Yunta et al 2005), anger (Stewart and McLean, 2005) and fear (Laros and Steenkamp, 2004). Reports of fear concerning genetically modified food (GMF) frequently appear in the mass media (Laros and Steenkamp, 2004), and the term "Frankenfoods" reflects opinions shared by many (Flores and Tobin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays we are witnesses that the transfer of biotechnology discoveries to crop production, industry, or medicine is not only restricted by the limiting factors of technology, underdeveloped scientific methods, or modes of scientific reasoning but also by ethics, morals, faith, the economy, environmental responsibility, risks, politics, education, etc. [1–8].…”
mentioning
confidence: 99%